Senegal’s agrifood system structure and drivers of transformation - Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Diao, Xinshen; Ellis, Mia (International Food Policy Research Institute, 2023)
Senegal experienced annual economic growth of 4.8 percent during the 2009 to 2019 period (World Bank 2023a). With an annual population growth rate of 2.7 percent over the same period, the living standards of Senegalese improved modestly. In 2020, the global COVID-19 pandemic caused a significant slowdown in economic growth, but growth rebounded in 2021. While the country was adversely affected by the global commodity market disruptions related to the Russia-Ukraine war that started in 2022 (Arndt et al. 2023; Diao and Thurlow 2023), its growth is projected to reach 8.0 percent in 2023 and 10.5 percent in 2024 (World Bank 2023b). This suggests a much-improved short-term outlook and a future growth trajectory well above its pre-pandemic growth trajectory. Agriculture is a relatively small sector in Senegal, accounting for less than one-fifth of GDP. However, the broader agrifood system (AFS), which includes processing, trade and transport of agrifood products, and food services, makes up about one-third of GDP. In this brief, we examine the performance of Senegal’s broader AFS and its contribution to growth and transformation.